Service quality: gaps in the Malaysian telemarketing industry - Kassim, N (2002)
Facing many rapid changes and challenges in the dynamic information technology environment, and the ever-increasing competitive pressures, many firms in telemarketing services have employed service quality as a principle competitive weapon. This study investigates the discrepancy between customer's expectation and perception towards the quality of services. Using the SERVQUAL instrument, this study uses simple random sampling to collect data from 100 users of telemarketing services throughout Malaysia. The results indicate that the sample population has perceptual problems with their telemarketing service experiences. Finally, strategic implications for the telemarketing companies involved and suggestions for future research are provided. (C) 2002 Elsevier Science Inc. All rights reserved.